2003
DOI: 10.1002/neu.10156
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ganglion cell production by notch signaling during retinal development

Abstract: Although progenitor cells in developing vertebrate retina are capable of producing all retinal cell types, they are competent to produce only certain cell types at a given time, and this competence changes as development progresses. We asked whether a change in progenitor cell competence is primarily responsible for ending production of a specific cell type, the retinal ganglion cell. Reducing Notch expression using an antisense oligonucleotide in vitro or in vivo increased ganglion cell genesis. The antisense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 41 publications
4
38
0
Order By: Relevance
“…Previous analyses of loss of Notch signaling during retinal development have consistently shown increased neural differentiation and inhibition of progenitors/gliogenesis (Dorsky et al, 1995;Austin et al, 1995;Tomita et al, 1996a;Henrique et al, 1997;Dorsky et al, 1997;Furukawa et al, 2000;Hojo et al, 2000;Satow et al, 2001;Silva et al, 2003;Takatsuka et al, 2004;Nelson et al, 2006;Jadhev et al, 2006;Yaron et al, 2006;Nelson et al, 2007a). Notch inactivation in early embryonic progenitors increases early retinal neurons (Nelson et al, 2007a), whereas Notch inactivation in later postnatal progenitors increases differentiation of late retinal cell types and decreases glial differentiation (Fig 8 A normal, Fig 8 B Notch inactivation in LP; Nelson et al, 2007a).…”
Section: Levels Of Notch Signaling Regulate Maintenance Of the Progenmentioning
confidence: 87%
See 1 more Smart Citation
“…Previous analyses of loss of Notch signaling during retinal development have consistently shown increased neural differentiation and inhibition of progenitors/gliogenesis (Dorsky et al, 1995;Austin et al, 1995;Tomita et al, 1996a;Henrique et al, 1997;Dorsky et al, 1997;Furukawa et al, 2000;Hojo et al, 2000;Satow et al, 2001;Silva et al, 2003;Takatsuka et al, 2004;Nelson et al, 2006;Jadhev et al, 2006;Yaron et al, 2006;Nelson et al, 2007a). Notch inactivation in early embryonic progenitors increases early retinal neurons (Nelson et al, 2007a), whereas Notch inactivation in later postnatal progenitors increases differentiation of late retinal cell types and decreases glial differentiation (Fig 8 A normal, Fig 8 B Notch inactivation in LP; Nelson et al, 2007a).…”
Section: Levels Of Notch Signaling Regulate Maintenance Of the Progenmentioning
confidence: 87%
“…Notch signaling maintains the progenitor pool during the course of retinal development, and regulates the evolutionary conserved sequence of progenitor cell differentiation into the six types of neurons and one type of glia (Dorsky et al, 1995;Austin et al, 1995;Tomita et al, 1996a;Henrique et al, 1997;Dorsky et al, 1997;Furukawa et al, 2000;Hojo et al, 2000;Satow et al, 2001;Silva et al, 2003;Takatsuka et al, 2004;Nelson et al, 2006;Jadhev et al, 2006;Yaron et al, 2006;Nelson et al, 2007a). While most of these studies have demonstrated key functions of Notch and the downstream signaling components in progenitor cells, relatively little attention has been given to upstream components, such as the source of Delta ligands and their respective regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Development 133 (7) Dorsky et al, 1997;Furukawa et al, 2000;Perron and Harris, 2000;Rapaport and Dorsky, 1998;Silva et al, 2003). In this case, it follows that premature loss of Notch1 activity in the RPCs of the peripheral retina during early embryogenesis (as in the Notch1 f/f ;␣-Cre mice) would result in the excessive differentiation of Notch1 -RPCs into cell types normally born during the corresponding early stages of retinogenesis: ganglion, cone, horizontal and amacrine cells (Fig.…”
Section: Research Articlementioning
confidence: 97%
“…Notch1 activity has been implicated in the inhibition of ganglion cell fate. This is based on the observation that ganglion cell production increases following antisense treatment of chick retinas with CNotch-1 or its ligand CDelta-1 (Ahmad et al, 1997;Austin et al, 1995;Silva et al, 2003). In contrast to these observations, analysis of the phenotype of Hes1 mutant embryos revealed premature differentiation of precursors into rod and horizontal cells (Tomita et al, 1996).…”
Section: Reduced Proliferation and Decreased Proportion Of Ganglion Amentioning
confidence: 99%
See 1 more Smart Citation